The Sedekah Bumi Tradition in Purwokerto Village, Lamongan : A Living Hadith Study - Massolihin, Edi; Bukhori, Ahmad; Sholihuddin, Ahmad; Royyan Faqih Azhary, Muhammad (Sekolah Tinggi Agama Islam Taruna Surabaya, 2026)
The sedekah bumi (earth alms) tradition is a cultural practice deeply rooted in Indonesia's agrarian society as an expression of gratitude for the harvest. This study aims to describe the application of the sedekah bumi tradition in Purwokerto Village, Ngimbang District, Lamongan Regency, explain the main motivations behind its implementation, and analyze the conformity of this practice with the guidance of the Prophet's hadith from a living hadith perspective. This research is field research using a descriptive qualitative approach. Data collection techniques were carried out through participant observation, semi-structured interviews with religious leaders, youth, and village elders, as well as documentation. Data analysis used the Miles and Huberman model, which consists of data reduction, data presentation, and conclusion drawing. The results show that the sedekah bumi tradition in Purwokerto Village has been passed down through generations as an expression of gratitude to Allah SWT as well as a form of respect for ancestors, especially the figure of Mbah Kaki Sari. The community's motivation to participate is multidimensional, including spiritual development, filling free time with positive activities, and strengthening social solidarity. This tradition is routinely carried out every Monday night after the Maghrib prayer on a rotating basis at residents' homes. From a living hadith perspective, this tradition is a concrete form of bringing the values of the Prophet's hadith to life, especially the hadith narrated by Muslim regarding seeking protection with the perfect words of Allah, the hadith narrated by al-Bukhari regarding protection from the severity of trials, the hadith narrated by al-Tirmidhi regarding total dependence on Allah, and the hadith narrated by Abu Dawud and Ibn Majah regarding prayers seeking Allah's help. The sedekah bumi tradition in Purwokerto Village proves that the Prophet's hadiths are not only understood as normative texts but are also brought to life in actual practice through adaptation to local culture and the social needs of the community.